Pancreatic fistula after gastrectomy. Retrospective single-center analysis - E. A. Toneev; E. A. Keshyan; D. I. Nuretdinov; A. A. Martynov; A. V. Zhinov; R. F. Shagdaleev (Сибирский онкологический журнал, 2024)
Objective: to determine the frequency and risk factors for postoperative pancreatic fistula (POPF) after gastrectomy. Material and Methods. From January 1, 2018 to October 31, 2023, 198 patients with stage I–III gastric cancer underwent gastrectomy with D2 lymphadenectomy at a Regional Oncological Dispensary. The characteristics of the studied patients were assessed according to a unified protocol. Statistically significant factors influencing the development of POPF were identified. Results. The incidence of POPF was 18.7 % (37/198). It was found that not all pancreatic fistulas were accompanied by acute pancreatitis. Among the patients with POPF, 5 had associated acute pancreatitis: 2 with mild, and 3 with moderate severity; no severe acute pancreatitis was observed. The statistically significant indicator for the occurrence of POPF was the neutrophil-lymphocyte index (p=0.033), in the absence of other infectious phenomena. In addition, the following significant factors were identified: lymphadenopathy of regional lymph nodes (p=0.037), tumor stage (T criterion) (p=0.002), splenectomy (p<0.001), and resection of the pancreas (p<0.001). Conclusion. The frequency of postoperative pancreatic fistulas after gastrectomy was 18.7 %. Statistically significant factors for the development of POPF include resection of the pancreas, splenectomy, lymph node status, tumor size, and depth of invasion. An additional indicator for the development of POPF is an increase in the neutrophil-lymphocyte index 1 day after surgery.